Incidence and outcomes of delirium in nonintubated critically ill patients: A prospective observational cohort study - Hari Naveen; Sooraj Kumar; Ramesh Venkataraman; Nagarajan Ramakrishnan; Bharath Kumar Tirupakuzhi Vijayaraghavan (Apollo Medicine, 2019)
Objective: Delirium in intubated patients is associated with worse outcomes. However, there is a paucity of data in nonintubated patients. Our study describes the incidence, risk factors, and outcomes for delirium for this population. Methods: We conducted a prospective observational study at a tertiary care intensive care unit (ICU). Data were collected over 2 months and delirium was screened using Confusion Assessment Method for the ICU tool. Only patients with at least 48 h stay in the ICU were included. Patient demographics, risk factors for delirium, and outcomes were recorded. Results: Among 75 patients screened, 13 patients (17.3%) screened positive for delirium. Delirium was more common in patients with higher disease severity and in those with a history of prior hospitalization. In addition, physical restraint use and neurological diagnoses also seemed to be associated with delirium. The presence of delirium did not affect key outcomes. Conclusion: Delirium is common among nonintubated critically ill patients and warrants routine monitoring.